Pelaksanaan Pengembangan Kurikulum Produktif Pendidikan Vokasional berdasarkan Sistem Manajemen Mutu ISO 9001:2008 - Andriani, Lusia (Program Studi Magister Pedagogi, 2014)
Lusia AndrianiSMK Putra Indonesia Malange-mail: andriani_lusia@yahoo.comAbstract:The approach of this research is descriptive qualitative method. The purpose of this research was to describe the planning, the implementation and the results of productive curriculum development in Vocational School of Putra Indonesia Malang based on Quality Management System ISO 9001:2008. The results of this research are 1) Planning the design, the general development of productive curriculum in accordance with ISO 9001:2008, which is kalusul 7.3. on curriculum development. 2) The implementation of productive curriculum in Vocational School of Putra Indonesia Malang, Generally, has been implemented based on ISO 9001:2008 management by concerning the compatibility between the implementation of learning process and curriculum development design. The realizations of every process are in making curriculum design, the syllabus arrangement, the arrangement of teaching materials, the arrangement of delivery methods, the arrangement of evaluation method. 3) The results of productive curriculum planning and implementation can be verified, the requirements used in accordance with the set design, able to show the profile of the required resources, able to realize the profile of graduates in accordance with curriculum design, and able to fulfill the demand of DU / DI / PT as stakeholders’ wish, implemented in accordance with the school's strategic plan.Keywords: curriculum development of productive, SMM ISO 9001:2008Abstrak:Pendekatan penelitian ini adalah metode deskriptif kualitatif. Tujuan penelitian ini untuk mendeskripsikan perencanaan, pelaksanaan dan hasil pengembangan kurikulum produktif di SMK Putra Indonesia Malang berdasarkan Sistem Manajemen Mutu ISO 9001:2008. Hasil penelitian ini adalah 1) Perencanaan desain, pengembangan kurikulum produktif secara umum sudah sesuai dengan SNI ISO 9001:2008, yaitu kalusul 7.3. tentang pengembangan kurikulum; 2) Pelaksanaan kurikulum produktif di SMK Putra Indonesia Malang, secara umum sudah dilaksanakan berdasarkan managemen ISO 9001:2008 yaitu dengan memperhatikan kesesuaian pelaksanaan proses pembelajaran dengan desain pengembangan kurikulum, keterlaksanaan setiap proses pembuatan desain kurikulum, penyusunan silabus, penyusunan bahan ajar, penyusunan metode penyampaian, penyusunan metode evaluasi; 3) Hasil perencanaan dan pelaksanaan kurikulum produktif dapat dilakukan verifikasi, syarat-syarat yang digunakan sesuai dengan desain yang ditetapkan, mampu menunjukan profil sumber daya yang diperlukan, mampu mewujudkan profil lulusan sesuai dengan desain kurikulum, dan mampu memenuhi permintaan DU/DI/PT sesuai keinginan stakeholder, dilaksanakan sesuai dengan rencana strategis sekolah.Kata kunci: pengembangan kurikulum produktif, SMM ISO 9001:2008